Pupils’ and parents’ opinions on schools with Italian as the language of instruction - Sorgo, Lara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2022)
The model of education in the ethnically mixed area of Slovene Istria is designed to ensure schooling for members of the Italian national community and their children in their own language, i.e., Italian. Although also attended by pupils of other nationalities, primary schools with Italian as the language of instruction are key for the preservation of Italian culture and language. The authors present selected research findings that shed light on the opinions of pupils and their parents on whether schools with Italian as the language of instruction develop pupils’ communicative competence in both Italian and Slovene, and whether the existing model of education creates conditions that promote the pupils’ awareness of the linguistic and cultural diversity of their environment. The results of the research reveal that the majority of the respondents consider competence in several languages an added value and that the model of education is adequate and good.
Keywords: jezikovna kompetenca; mnenje učencev in staršev; osnovne šole z italijanskim učnim jezikom; slovenska Istra